Bipolarisation of the Moroccan political party arena? Refuting this idea through an analysis of the party system. Issue 1 (2nd January 2021) - Szmolka, Inmaculada
ABSTRACT: The campaign for the October 7, 2016 election of the Moroccan House of Representatives, during which media attention was focused on the competition between the Islamist Party of Justice and Development (PJD) and the secular Party of Authenticity and Modernity (PAM), resulted in a narrow victory of the former over the latter. This led journalists and scholars to speak of a 'bipolarisation' of the political party arena in Morocco. This article aims to empirically verify such assertion by analysing the characteristics of the party system that emerged out of the Moroccan 2016 elections. Findings reveal that, despite the high party system fragmentation and the ideological and political differences between the PJD and PAM, the Moroccan party system cannot be classified as bipolar for three main reasons: there are no alliances or coalitions of opposing parties that are stable over time, and that alternate in the government; third political parties possess political 'blackmail' and coalition potential in the process of government formation; and the direction of party competition is centripetal, given the need for parties to be moderate if they wish to gain influence within the political system. The authoritarian nature of the political regime and the 'executive monarchy' form of government are the core factors that account for the absence of bipolarisation within the Moroccan party system.